1999
DOI: 10.4269/ajtmh.1999.60.630
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of Venezuelan equine encephalitis virus subtype IE genotypes in Central America and Mexico.

Abstract: Phylogenetic analysis of 20 strains of Venezuelan equine encephalitis (VEE) virus subtype IE isolated from 1961 to 1996 in Mexico and throughout Central America showed that VEE virus subtype IE was monophyletic with respect to other VEE virus subtypes. Nonetheless, there were at least three distinct geographically separated VEE virus IE genotypes: northwestern Panama, Pacific coast (Mexico/Guatemala), and Gulf/Caribbean coast (Mexico/ Belize). Strains from the Caribbean coast of Guatemala, Honduras, and Nicara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 35 publications
2
25
1
Order By: Relevance
“…Previous data from partial PE2 sequences suggested that the enzootic isolate, 80U76, was the virus most closely related to the four epizootic IE virus strains (29). In contrast, our complete genomic sequences indicate that, in a pairwise comparison with the four epizootic Mexican IE viruses, enzootic strain 68U201 shared a greater nucleotide and amino acid sequence identity than the 1980 isolate that was made from the same sylvatic focus at La Avellana, Guatemala ( Table 1).…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…Previous data from partial PE2 sequences suggested that the enzootic isolate, 80U76, was the virus most closely related to the four epizootic IE virus strains (29). In contrast, our complete genomic sequences indicate that, in a pairwise comparison with the four epizootic Mexican IE viruses, enzootic strain 68U201 shared a greater nucleotide and amino acid sequence identity than the 1980 isolate that was made from the same sylvatic focus at La Avellana, Guatemala ( Table 1).…”
Section: Resultscontrasting
confidence: 50%
“…Previous sequencing studies of the N terminus of the PE2 envelope glycoprotein precursor gene of many enzootic and epizootic VEE subtype IE viruses indicated a high degree of genetic similarity (less than 1% nucleotide sequence divergence) between isolates obtained from the two recent Mexican outbreaks and enzootic isolates taken from sylvatic habitats on the Pacific Coast of Guatemala (29). Based on this high genetic similarity between enzootic and epizootic subtype IE VEEV, we hypothesized that the emergence of epizootic subtype IE viruses could have resulted in a similar manner as epizootic IAB or IC viruses, from enzootic progenitors.…”
mentioning
confidence: 99%
“…This is a significant finding considering that in 1993 and 1996, IE VEE viruses caused outbreaks of equine encephalitis in southern Mexico, with over 160 cases documented (21). Utilizing multiple approaches to characterize genotypic markers associated with virulence, chimeric viruses should be a useful approach for elucidating genetic determinants involved in pathogenesis, transmission, and evolution of the multiple subtypes and varieties of the VEE antigenic complex.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally transmitted by mosquitoes through rodent hosts, VEEV is highly pathogenic for equines and humans and has sporadically caused widespread epidemics in North, Central, and South America (48). While most equine and human outbreaks have been caused by the epizootic IAB and IC subtypes of VEEV, isolated cases of disease caused in equines and humans by infection with the enzootic ID and IE subtypes have also been reported (10,32,50). Regardless of the variety, human infection with VEEV typically results in an acute, incapacitating, but self-limiting disease characterized by fever, headache, lymphopenia, myalgia, and malaise (3).…”
mentioning
confidence: 99%